Children and sexting: The case for intergenerational co-learning. (August 2018) - Lee, Nick; Hewett, Angela; Rübner Jørgensen, Clara; Turner, Jerome; Wade, Alex; Weckesser, Annalise
Children's sexting is presented as an emergent outcome of technology-based innovation in children's peer-to-peer relations. We argue that it calls for creative responses that draw on adults' and children's understandings and views and on exchanges of these. We describe, and make the case for, intergenerational co-learning as a practice that could foster such creativity, as a pathway for children's participation in the debate, and as a means by which media regulators, children's service providers, and social media companies can consider and address their capabilities and responsibilities.